Nano aluminum oxide polishing solution for silicon carbide substrate slice as well as preparation method and application of nano aluminum oxide polishing solution
By using the hierarchical aluminum oxide polishing fluid prepared by the hierarchical α-Al2O3 abrasive particles and potassium permanganate oxide, chemical mechanical polishing of silicon carbide lining film solves the problem of high time cost and low material removal rate in the existing technology. Implement efficient removal and smooth surface treatment.
Patent Information
- Application Number
- CN202411481814.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The polishing process of existing silicon carbide substrate sheets has problems such as high time cost, low material removal rate, and difficult surface roughness to meet actual needs.
Classified α-Al2O3 is used as the abrasive grain for silicon carbide polishing, combined with potassium permanganate as the oxidant, to prepare nano-alumina polishing liquid, and improve the material removal rate and surface smoothness of the silicon carbide substrate through chemical mechanical polishing technology.
Efficient removal and surface smoothing of silicon carbide substrates are achieved. The material removal rate is 1.000-1.500μm/h, and the surface roughness is reduced to 0.065-0.075nm, which meets the polishing requirements of high-precision workpieces.
Smart Images

Figure BDA0005097603010000081 
Figure BDA0005097603010000131 
Figure BDA0005097603010000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material polishing, and in particular to a nano-aluminum oxide polishing liquid for silicon carbide substrate sheets, and a preparation method and application thereof. Background Art
[0002] As a representative of the third generation of semiconductor materials, silicon carbide has more excellent physical, chemical and electrical properties, and is widely used in the electric vehicle industry, new energy, 5G communications, national defense and other fields. In addition, according to the different electrical conductivity, silicon carbide is divided into conductive silicon carbide and semi-insulating silicon carbide. Conductive silicon carbide wafers are mainly used in the manufacture of high-temperature, high-voltage, and electrical-resistant power devices. The main application areas include new energy vehicles, rail transportation, photovoltaic power generation, aerospace, smart grids, etc.
[0003] The third-generation semiconductor material silicon carbide (C) has better physical, chemical and electrical properties than the first-generation semiconductor materials (Si) and the second-generation semiconductor materials (GaAs, InP, etc.). Silicon carbide has excellent physical properties such as high hardness (Mohs hardness 9.5, second only to diamond's 10), high strength (high bending strength and tensile strength, which can reach 300-500MPa; high crack resistance, which can reach 200-1000MPa), high modulus (up to 400-500GPa), high thermal conductivity (4.9W / cm·K), and high temperature resistance (melting point up to 2730℃); it has excellent chemical properties such as high corrosion resistance (resistance to strong acid corrosion, strong alkali corrosion, and hydrothermal corrosion) and high chemical stability; it has excellent electrical properties such as high bandgap width (3.3eV), high breakdown electric field (3.0MV / cm), low electron mobility (<400cm2·V-1), low hole mobility (<90cm2·V-1), and high saturation migration velocity (2.0×107cm / s). In addition, silicon carbide is in greater demand in the manufacture of RF devices and power devices due to its lower impedance, which can reduce product size and improve conversion efficiency; higher frequency can reduce energy loss; and it can withstand more extreme working environments. It is widely used in the electric vehicle industry, new energy, 5G communications, national defense and other fields.
[0004] Silicon carbide has many crystal forms, such as 3C, 4H, 6H, 9R, 15R, etc., where (C), (H), and (R) represent cubic, hexagonal, and rhombus, respectively. However, in different silicon carbide crystal forms, different electronic potentials lead to different electronic band structures, and their optical properties, electrical properties, etc. are also significantly different. Compared with crystalline silicon carbide such as 3C-SiC and 6H-SiC, 4H-SiC has a higher bandgap and a higher breakdown electric field, and is more suitable for the manufacture of high-frequency, high-temperature, and high-power devices. Due to the rise of new energy vehicles, the demand for conductive silicon carbide wafers is increasing. As an important step in the production process of silicon carbide devices, the key parameters such as surface roughness of silicon carbide substrates will directly affect the performance of silicon carbide devices. Therefore, during the polishing process, the requirements of the subsequent process for the base surface roughness must be met. As a comprehensive flattening technology, chemical mechanical polishing has been widely used in the polishing process of silicon carbide substrates.
[0005] Since silicon carbide has a high Mohs hardness, the Mohs hardness of silicon dioxide and cerium dioxide, which are commonly used as silicon carbide polishing abrasives, is only 7. Using them in chemical mechanical polishing (CMP) can still produce qualified 4H-SiC substrates, but the low MRR means that the CMP step requires extremely high time costs and is increasingly unable to meet actual requirements.
[0006] Patent publication number CN111073520A discloses a polishing powder for polishing silicon carbide wafers and a preparation method and a polishing liquid thereof. The preparation method of the polishing powder for polishing silicon carbide wafers comprises the following steps: S1, respectively preparing liquid A, micron α-alumina dispersion liquid, and liquid B, a potassium hydroxide aqueous solution containing sodium metaaluminate; S2, adding liquid B and hydrochloric acid to liquid A at a certain reaction temperature, continuing to stir for a period of time after adding liquid B and hydrochloric acid, obtaining a slurry of micron α-alumina coated with aluminum hydroxide, and then aging treatment; S3, adding nano α-alumina powder to the aged slurry while stirring, continuing to stir for a period of time after adding nano α-alumina powder, obtaining a slurry of nano α-alumina coated with aluminum hydroxide coated with micron α-alumina; S4, separating the above slurry and drying it, then calcining it at a high temperature, and then post-processing it to obtain polishing powder. The process conditions are complex, the preparation cost is high, and the service life is short. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the prior art and provide a nano-alumina polishing liquid for silicon carbide substrates and a preparation method and application thereof, and select graded α-Al 2 O 3As abrasive grains for silicon carbide polishing, potassium permanganate with stronger oxidizing properties is selected as an oxidant. The prepared nano-alumina polishing liquid will be used in the chemical mechanical polishing of silicon carbide substrates. While increasing the silicon surface material removal rate of the silicon carbide substrate, its surface roughness is reduced, and an atomic-level smooth surface quality is obtained.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] One of the technical solutions of the present invention is to provide a nano-alumina polishing liquid for silicon carbide substrates, comprising α-Al 2 O 3 0.5wt% to 6.0wt% of abrasive, 0.5wt% to 5.0wt% of oxidant, 0.1wt% to 1.0wt% of co-oxidant, 0.05wt% to 0.5wt% of pH adjuster, 0.10wt% to 0.50wt% of dispersant, and the balance is water;
[0010] The α-Al 2 O 3 The abrasive D10 is 0.100-0.140 μm, D50 is 0.180-0.230 μm, D90 is 0.240-0.300 μm, D100 is 0.340-0.420 μm, and the diameter distance is 0.6-0.9.
[0011] Furthermore, the α-Al 2 O 3 The preparation method of abrasive is as follows: 2 O 3 Powder is formulated into α-Al 2 O 3 The slurry was ground after adding potassium citrate. 2 O 3 The slurry is homogenized to obtain α-Al 2 O 3 Abrasive.
[0012] Furthermore, the α-Al 2 O 3 The solid content of the slurry is 20% to 50%;
[0013] The mass of potassium citrate is 2 O 3 1% to 5% of powder mass.
[0014] Furthermore, the α-Al 2 O 3 The purity of the powder is greater than 99.99%.
[0015] Furthermore, the frosted α-Al2 O 3 α-Al in slurry 2 O 3 The average particle size is 200-300nm.
[0016] Furthermore, the specific parameters of the frosting are: zirconia bead size 0.20.1-0.6 mm, filling rate 70%-85%, rotation speed 1000-3500 rpm, linear speed 5-10 m / s, flow rate 80-120 L / h, time 80-150 min.
[0017] Furthermore, the specific process of the homogenization treatment is as follows: taking the frosted α-Al 2 O 3 The slurry is centrifuged at 1000-3000 rpm for 1-10 minutes to obtain an upper slurry, a middle slurry and a lower slurry. The middle slurry is filtered to obtain the α-Al 2 O 3 Abrasives;
[0018] The average particle size of the upper slurry layer is less than 100 nm, the average particle size of the middle slurry layer is 100-250 nm, and the average particle size of the lower slurry layer is greater than 250 nm;
[0019] The filtration includes primary filtration and secondary filtration, wherein the primary filtration is filtration using a filter bag, and the secondary filtration is filtration using a microporous filter element.
[0020] Furthermore, the middle layer slurry is filtered, and the filtered product is the α-Al 2 O 3 The abrasive is discarded as the retained filter residue. The middle layer slurry used is α-Al 2 O 3 The main part of the slurry, the particle size of the upper slurry is less than 100nm, accounting for only α-Al 2 O 3 A very small part of the slurry, less than 10%, can be used for chemical mechanical polishing experiments on silicon carbide substrates, but α-Al 2 O 3 The slurry utilization rate is low, the waste is serious, and the material removal rate after polishing is low, which is difficult to meet actual needs.
[0021] Furthermore, the upper slurry can be recycled and used for other fine processing of the silicon carbide substrate, such as fine polishing. Fine polishing refers to a chemical mechanical polishing method that has higher requirements on the surface quality of the silicon carbide substrate. If the upper slurry is used to chemically mechanically polish the silicon surface of the silicon carbide substrate, its surface quality is higher, and the surface roughness is about 0.02nm.
[0022] Furthermore, the lower slurry can be recycled for continuing other operations, such as sand grinding experiments.
[0023] Furthermore, the filter bag is made of non-woven fabric with a pore size of 0.5 to 1.0 μm.
[0024] Furthermore, the microporous filter element is made of polypropylene and has a pore size of 0.5 to 1.0 μm.
[0025] Furthermore, the oxidant includes potassium permanganate, sodium permanganate, sodium persulfate, hydrogen peroxide, and ammonium hypochlorite, preferably potassium permanganate. Potassium permanganate, as a strong oxidant, can oxidize and corrode the surface of the silicon carbide substrate with high hardness (Mohs hardness of 9) to form a soft silicon dioxide layer with low hardness (Mohs hardness of 6), thereby reducing the difficulty of processing the surface of the silicon carbide substrate;
[0026] The pH regulator includes nitric acid, potassium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium tetraborate;
[0027] The dispersant includes sodium hexametaphosphate, sodium silicate, potassium citrate, sodium polyacrylate, sodium salt of maleic acid acrylic acid copolymer, and polyethylene glycol.
[0028] The co-oxidant includes calcium nitrate, which is helpful to increase the service life of the nano-alumina polishing liquid when combined with the oxidant.
[0029] The second technical solution of the present invention is to provide a method for preparing a nano-alumina polishing liquid for a silicon carbide substrate, wherein α-Al 2 O 3 The abrasive, oxidant, pH regulator, dispersant and water are stirred according to mass percentage and mixed evenly to obtain the nano-alumina polishing liquid.
[0030] The third technical solution of the present invention is to provide an application of a nano-alumina polishing liquid for a silicon carbide substrate, and the silicon carbide substrate is chemically mechanically polished using the nano-alumina polishing liquid.
[0031] Furthermore, the specific parameters of the chemical mechanical polishing are: polishing pressure of 10-15 psi, lower plate rotation speed of 20-60 rpm, polishing liquid flow rate of 0.5-1.5 L / min, and polishing time of 0.5-5 h.
[0032] A fourth technical solution of the present invention is to provide a silicon carbide substrate sheet, which is obtained by chemical mechanical polishing using the nano-alumina polishing liquid. After the chemical mechanical polishing is completed, the surface is cleaned to remove the aluminum oxide particles remaining on the surface to obtain a silicon carbide substrate sheet.
[0033] Furthermore, the material removal rate (MRR) of the silicon carbide substrate sheet is 1.000-1.500 μm / h, and the surface roughness (Ra) is 0.065-0.075 nm.
[0034] Compared with the prior art, the present invention has the following advantages:
[0035] (1) The present invention selects α-Al 2 O 3 The powder is made into alumina slurry and then sand-milled. 2 O 3 The slurry is homogenized to obtain α-Al with narrower and more uniform particle size distribution. 2 O 3 Abrasive. Use homogenized α-Al 2 O 3 The slurry is abrasive, and additives such as oxidant, pH adjuster, dispersant, etc. are added to prepare nano-alumina polishing liquid to perform chemical mechanical polishing on silicon carbide substrates. Silicon carbide substrates with high MRR and low Ra can be obtained, with MRR of 1.000-1.500 μm / h and Ra of 0.065-0.075 nm.
[0036] (2) The alumina particles usually prepared or sand-milled do not have a single particle size, but rather a state of having a wide particle size distribution. 2 O 3 The particles are homogenized to separate the alumina particles with an average particle size less than 100nm and those with an average particle size greater than 250nm, leaving the α-Al2O3 particles with a narrow particle size distribution and relatively uniform particle size. 2 O 3 The slurry can be used in chemical mechanical polishing experiments of silicon carbide substrates to effectively avoid scratches on the silicon carbide substrate caused by large particles. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0038] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.
[0039] In the following examples, the particle size distribution was tested using a Bettersize 2600 laser particle size distribution analyzer model BT-802 provided by Bettersize Electronic Technology (Shanghai) Co., Ltd.
[0040] The surface morphology of the alumina particles was tested using a scanning electron microscope (ZEISS Gemini SEM 300, Germany) provided by Carl Zeiss (Shanghai) Management Co., Ltd.
[0041] The surface roughness was tested using an atomic force microscope (DIMENSION EDGE System) provided by Shanghai Shuoyi Testing Technology Co., Ltd.
[0042] The polishing liquid prepared by the present invention was subjected to a chemical mechanical polishing experiment using a single-sided polishing machine of model ES32B from Zhejiang Morinaga Optoelectronic Equipment Co., Ltd. The polishing machine parameters were set as follows: polishing pressure of 10.873 psi, lower plate speed of 40 rpm, polishing liquid flow rate of 1 L / min, and polishing time of 1 h; the polishing pad was a non-woven fabric polishing pad of model NWS-85 from Quzhou Bolai Narun Electronic Materials Co., Ltd. The silicon carbide substrate was a 6-inch 4H-SiC substrate from Shanxi Shuoke Crystal Co., Ltd.
[0043] A nano-alumina polishing liquid for silicon carbide substrate, comprising α-Al 2 O 3 0.5wt% to 6.0wt% of abrasive, 0.5wt% to 5.0wt% of oxidant, 0.1wt% to 1.0wt% of co-oxidant, 0.05wt% to 0.5wt% of pH adjuster, 0.10wt% to 0.50wt% of dispersant, and the balance is water;
[0044] The α-Al 2 O 3 The abrasive D10 is 0.100-0.140 μm, D50 is 0.180-0.230 μm, D90 is 0.240-0.300 μm, D100 is 0.340-0.420 μm, and the diameter distance is 0.6-0.9.
[0045] As one of the preferred embodiments, the α-Al 2 O 3 The preparation method of abrasive is as follows: 2 O 3 Powder is formulated into α-Al 2 O 3 The slurry was ground after adding potassium citrate. 2 O 3 The slurry is homogenized to obtain α-Al 2 O 3Abrasive.
[0046] As one of the preferred embodiments, the α-Al 2 O 3 The solid content of the slurry is 20% to 50%;
[0047] The mass of potassium citrate is 2 O 3 1% to 5% of powder mass.
[0048] As one of the preferred embodiments, the α-Al 2 O 3 The purity of the powder is greater than 99.99%.
[0049] As one of the preferred embodiments, the frosted α-Al 2 O 3 α-Al in slurry 2 O 3 The average particle size is 200-300nm.
[0050] As one of the preferred implementations, the specific parameters of the frosting are: zirconia bead size 0.20.1-0.6 mm, filling rate 70%-85%, rotation speed 1000-3500 rpm, linear speed 5-10 m / s, flow rate 80-120 L / h, time 80-150 min.
[0051] As one of the preferred embodiments, the specific process of the homogenization treatment is as follows: take the frosted α-Al 2 O 3 The slurry is centrifuged at 1000-3000 rpm for 1-10 minutes to obtain an upper slurry, a middle slurry and a lower slurry. The middle slurry is filtered to obtain the α-Al 2 O 3 Abrasives;
[0052] The average particle size of the upper slurry layer is less than 100 nm, the average particle size of the middle slurry layer is 100-250 nm, and the average particle size of the lower slurry layer is greater than 250 nm;
[0053] The filtration includes primary filtration and secondary filtration, wherein the primary filtration is filtration using a filter bag, and the secondary filtration is filtration using a microporous filter element.
[0054] As one of the preferred embodiments, the middle layer slurry is filtered, and the filtered product is the α-Al 2 O 3 The abrasive is discarded as the retained filter residue. The middle layer slurry used is α-Al 2 O 3The main part of the slurry, the particle size of the upper slurry is less than 100nm, accounting for only α-Al 2 O 3 A very small part of the slurry, less than 10%, can be used for chemical mechanical polishing experiments on silicon carbide substrates, but α-Al 2 O 3 The slurry utilization rate is low, the waste is serious, and the material removal rate after polishing is low, which is difficult to meet actual needs.
[0055] As one of the preferred embodiments, the upper slurry can be recycled and used for other fine processing of the silicon carbide substrate, such as fine polishing, so as not to waste raw materials. Fine polishing refers to a chemical mechanical polishing method that has higher requirements on the surface quality of the silicon carbide substrate. If the upper slurry is used to chemically mechanically polish the silicon surface of the silicon carbide substrate, its surface quality is higher, and the surface roughness is about 0.02nm.
[0056] As one of the preferred embodiments, the lower layer slurry can be recycled and used to continue other operations, thereby avoiding waste of raw materials, such as sand grinding experiments.
[0057] As one of the preferred embodiments, the filter bag is made of non-woven fabric with a pore size of 0.5 to 1.0 μm.
[0058] As one of the preferred embodiments, the microporous filter element is made of polypropylene and has a pore size of 0.5 to 1.0 μm.
[0059] As one of the preferred embodiments, the oxidant includes potassium permanganate, sodium permanganate, sodium persulfate, hydrogen peroxide, and ammonium hypochlorite, preferably potassium permanganate. Potassium permanganate, as a strong oxidant, can oxidize and corrode the surface of the silicon carbide substrate with high hardness (Mohs hardness of 9) to form a soft silicon dioxide layer with low hardness (Mohs hardness of 6), thereby reducing the difficulty of processing the surface of the silicon carbide substrate;
[0060] The pH regulator includes nitric acid, potassium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium tetraborate;
[0061] The dispersant includes sodium hexametaphosphate, sodium silicate, potassium citrate, sodium polyacrylate, sodium salt of maleic acid acrylic acid copolymer, and polyethylene glycol.
[0062] The co-oxidant includes calcium nitrate, which is helpful to increase the service life of the nano-alumina polishing liquid when combined with the oxidant.
[0063] A method for preparing a nano-alumina polishing liquid for a silicon carbide substrate, comprising: 2 O 3The abrasive, oxidant, pH regulator, dispersant and water are stirred according to mass percentage and mixed evenly to obtain the nano-alumina polishing liquid.
[0064] The invention discloses an application of nano-alumina polishing liquid for silicon carbide substrate sheets, wherein the nano-alumina polishing liquid is used to perform chemical mechanical polishing on the silicon carbide substrate sheets.
[0065] As one of the preferred implementations, the specific parameters of the chemical mechanical polishing are: polishing pressure of 10-15 psi, lower plate rotation speed of 20-60 rpm, polishing liquid flow rate of 0.5-1.5 L / min, and polishing time of 0.5-5 h.
[0066] A silicon carbide substrate sheet is obtained by chemical mechanical polishing with the nano-alumina polishing liquid. After the chemical mechanical polishing is completed, the surface is cleaned to remove the aluminum oxide particles remaining on the surface to obtain the silicon carbide substrate sheet.
[0067] As one of the preferred implementations, the material removal rate (MRR) of the silicon carbide substrate sheet is 1.000-1.500 μm / h, and the surface roughness (Ra) is 0.065-0.075 nm.
[0068] Example 1
[0069] This embodiment provides a nano-alumina polishing liquid for silicon carbide substrates and a preparation method and application thereof, wherein the preparation method comprises the following steps:
[0070] (1) Preparation of α-Al 2 O 3 Abrasive
[0071] High purity α-Al 2 O 3 The powder was prepared into α-Al with a solid content of 30 wt%. 2 O 3 Slurry, α-Al 2 O 3 Adding α-Al 2 O 3 The powder weight was 2% potassium citrate, stirred for 30 minutes, and sanded with a sand mill. The sanding parameters were: zirconia bead size 0.2 mm, filling rate 75 wt%, rotation speed 3000 rpm, linear speed 10.26 m / s, flow rate 120 L / h, and time 80 minutes. The model of the sand mill was SMP 0.5, and the manufacturer was Husong Intelligent Equipment (Taicang) Co., Ltd. 2 O 3 The powder comes from 3000 mesh high-purity alumina powder provided by Yangzhou Dilan Chemical Materials Co., Ltd.
[0072] After sand grinding, α-Al 2 O 3 The slurry was homogenized. The homogenization method was as follows: ① Take 8 50 mL centrifuge tubes and mix the sand-ground α-Al 2 O 3 The slurry is filled and centrifuged on a desktop centrifuge. The centrifuge parameters are: speed 1500rpm, time 5min; after the centrifugation, the upper slurry, the middle slurry and the lower slurry are obtained. The average particle size of the upper slurry is less than 100nm, the average particle size of the middle slurry is 100-250nm, and the average particle size of the lower slurry is greater than 250nm; the middle slurry is taken; ② the middle slurry after centrifugal classification is filtered, filtered twice with a filter bag, and then filtered twice with a microporous filter element. The filtered product is the α-Al 2 O 3 Abrasive. The model of the desktop centrifuge is TDL-40B, and the manufacturer is Shanghai Anting Scientific Instrument Co., Ltd.; the model of the filter bag is No. 1 180*430 0.5 micron, and the manufacturer is Shanghai Fuxin Environmental Protection Technology Co., Ltd.; the model of the microporous filter element is K68B-2H-M10﹡10″(1μm), and the manufacturer is Hangzhou Cosma Membrane Technology Co., Ltd.
[0073] (2) Preparation of nano-alumina polishing liquid
[0074] Weigh 3760g of deionized water, add 60g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 150g of α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt % nitric acid was used to adjust the pH of the solution to 9. After stirring evenly, a nano-alumina polishing liquid (potassium permanganate content of 1.5 wt %, α-Al 2 O 3 The abrasive content is 0.75wt%, the aluminum nitrate nonahydrate content is 0.25wt%, the calcium nitrate tetrahydrate content is 0.25wt%, and the sodium silicate content is 0.25wt%).
[0075] (3) Chemical mechanical polishing of silicon carbide substrate
[0076] The Si surface of the silicon carbide substrate was chemically mechanically polished using 4 kg of the prepared nano-alumina polishing liquid, with a polishing pressure of 10.873 psi, a lower plate speed of 40 rpm, a polishing liquid flow rate of 1 L / min, and a polishing time of 1 h. The polishing pad was a non-woven polishing pad of model NWS-85 from Quzhou Bolai Narun Electronic Materials Co., Ltd. The silicon carbide substrate was a 6-inch 4H-SiC substrate from Shanxi Shuoke Crystal Co., Ltd.
[0077] 4 kg of nano-alumina polishing liquid was recycled and polished continuously for 4×1 h. The mass of the silicon carbide substrate was weighed after each hour of polishing. The MRRs were 1.121 μm / h, 1.040 μm / h, 1.029 μm / h, and 1.011 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.068 nm.
[0078] The calculation formula for MRR is as follows:
[0079]
[0080] Wherein, △m is the mass difference of the silicon carbide substrate before and after polishing (g), ρ is the density of the silicon carbide substrate (3.2 g / cm3), s is the area of the Si surface of the silicon carbide substrate (Π×7.52, cm2), and t is the polishing time (h).
[0081] Example 2
[0082] Compared with Example 1, most of them are the same, except that in step (2) of preparing the nano-alumina polishing liquid:
[0083] Weigh 3730g of deionized water, add 40g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 200g of the homogenized α-Al 2 O 3 Abrasive (solid content 20%) was added to the stirred potassium permanganate solution, 10 g of sodium silicate was added, and after it was completely dissolved, 20 wt % nitric acid was used to adjust the pH of the solution to 9, and after stirring evenly, a nano-alumina polishing liquid (containing 1.0 wt % potassium permanganate and 1.0 wt % α-Al 2 O 3 The abrasive content is 1 wt%, the aluminum nitrate nonahydrate content is 0.25 wt%, the calcium nitrate tetrahydrate content is 0.25 wt%, and the sodium silicate content is 0.25 wt%).
[0084] 4 kg of polishing liquid was recycled and polished continuously for 4×1 h. The substrate was weighed after each hour of polishing. The MRRs were 1.618 μm / h, 1.487 μm / h, 1.335 μm / h, and 1.188 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.070.
[0085] Example 3
[0086] Compared with Example 1, most of them are the same, except that in step (2) of preparing the nano-alumina polishing liquid:
[0087] Weigh 3490g of deionized water, add 80g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 400g of the homogenized α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt% nitric acid was used to adjust the pH of the solution to 9. After stirring evenly, a nano-alumina polishing liquid (including 2.0 wt% potassium permanganate and α-Al 2 O 3 The abrasive content is 2.0wt%, the aluminum nitrate nonahydrate content is 0.25wt%, the calcium nitrate tetrahydrate content is 0.25wt%, and the sodium silicate content is 0.25wt%).
[0088] 4 kg of polishing liquid was recycled and polished continuously for 4×1 h. The substrate was weighed after each hour of polishing. The MRRs were 1.699 μm / h, 1.542 μm / h, 1.406 μm / h, and 1.204 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.072.
[0089] Example 4
[0090] Compared with Example 1, most of them are the same, except that in step (2) of preparing the nano-alumina polishing liquid:
[0091] Weigh 3250g of deionized water, add 120g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 600g of the homogenized α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt% nitric acid was used to adjust the pH value of the solution to 9. After stirring evenly, a nano-alumina polishing liquid (wherein the potassium permanganate content was 3.0 wt%, α-Al 2 O 3 The abrasive content is 3.0wt%, the aluminum nitrate nonahydrate content is 0.25wt%, the calcium nitrate tetrahydrate content is 0.25wt%, and the sodium silicate content is 0.25wt%).
[0092] 4 kg of polishing liquid was recycled and polished continuously for 4×1 h. The substrate was weighed after each hour of polishing. The MRRs were 1.524 μm / h, 1.423 μm / h, 1.231 μm / h, and 1.204 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.073 nm.
[0093] Example 5
[0094] Compared with Example 1, most of them are the same, except that in step (2) of preparing the nano-alumina polishing liquid:
[0095] Weigh 3760g of deionized water, add 160g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 800g of the homogenized α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt% nitric acid was used to adjust the pH of the solution to 8. After stirring evenly, a nano-alumina polishing liquid (containing 4.0 wt% potassium permanganate and α-Al 2 O 3 The abrasive content is 4.0wt%, the aluminum nitrate nonahydrate content is 0.25wt%, the calcium nitrate tetrahydrate content is 0.25wt%, and the sodium silicate content is 0.25wt%).
[0096] 4 kg of polishing liquid was recycled and polished continuously for 4×1 h. The substrate was weighed after each hour of polishing. The MRRs were 1.134 μm / h, 1.204 μm / h, 1.145 μm / h, and 1.201 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.069 nm.
[0097] Example 6
[0098] Compared with Example 1, most of them are the same, except that in step (2) of preparing the nano-alumina polishing liquid:
[0099] Weigh 2770g of deionized water, add 200g of potassium permanganate and 20g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 1000g of the homogenized α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt% nitric acid was used to adjust the pH of the solution to 9. After stirring evenly, a nano-alumina polishing liquid (wherein the potassium permanganate content was 5.0 wt%, α-Al 2 O 3 The abrasive content is 5.0 wt%, the calcium nitrate tetrahydrate content is 0.5 wt%, and the sodium silicate content is 0.25 wt%).
[0100] 4 kg of polishing liquid was recycled and polished continuously for 4×1 hour. The substrate was weighed after each hour of polishing. The MRRs were 1.156 μm / h, 1.211 μm / h, 1.102 μm / h, and 1.123 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.067 nm.
[0101] Example 7
[0102] Compared with Example 1, most of them are the same, except that in step (2) of preparing the nano-alumina polishing liquid:
[0103] Weigh 2710g of deionized water, add 60g of potassium permanganate and 20g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 1200g of the homogenized α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt% nitric acid was used to adjust the pH of the solution to 9. After stirring evenly, a nano-alumina polishing liquid (containing 1.5 wt% potassium permanganate and 1.5 wt% α-Al 2 O 3 The abrasive content is 6.0 wt%, the calcium nitrate tetrahydrate content is 0.5 wt%, and the sodium silicate content is 0.25 wt%).
[0104] 4 kg of polishing liquid was recycled and polished continuously for 4×1 hour. The substrate was weighed after each hour of polishing. The MRRs were 1.312 μm / h, 1.256 μm / h, 1.234 μm / h, and 1.179 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.066 nm.
[0105] Comparative Example 1
[0106] This comparative example provides a nano-silica sol polishing liquid for silicon carbide substrates and a preparation method and application thereof, wherein the preparation process comprises the following steps:
[0107] Weigh 3796.66g of deionized water, add 40g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, use potassium hydroxide to adjust the pH of the solution to 7.5, then weigh 133.34g of silica sol (solid content 30wt%) and add it to the stirring potassium permanganate solution, add 10g of sodium silicate, and after it is completely dissolved, use 20wt% nitric acid to adjust the pH of the solution to 9, and stir evenly to obtain a nano-silica sol polishing liquid (wherein the potassium permanganate content is 1.0wt%, the silicon dioxide content is 1.0wt%, the aluminum nitrate nonahydrate content is 0.25wt%, the calcium nitrate tetrahydrate content is 0.25wt%, and the sodium silicate content is 0.25wt%). The silica sol model is WY-145, and the manufacturer is Quzhou Bolai Narun Electronic Materials Co., Ltd.
[0108] The Si surface of the silicon carbide substrate was chemically mechanically polished using 4 kg of the prepared nano-silica sol polishing liquid, with a polishing pressure of 10.873 psi, a lower plate speed of 40 rpm, a polishing liquid flow rate of 1 L / min, and a polishing time of 1 h. The polishing pad was a non-woven polishing pad of model NWS-85 from Quzhou Bolai Narun Electronic Materials Co., Ltd. The silicon carbide substrate was a 6-inch 4H-SiC substrate from Shanxi Shuoke Crystal Co., Ltd.
[0109] 4 kg of nano-silica sol polishing liquid was recycled and polished continuously for 4×1 hour. The mass of the silicon carbide substrate was weighed after each hour of polishing. The MRR was 0.805 μm / h, 0.786 μm / h, 0.765 μm / h, and 0.742 μm / h. The surface roughness Ra measured by atomic force microscopy was 0.126 nm.
[0110] Comparative Example 2
[0111] This comparative example provides a nano-alumina polishing liquid for silicon carbide substrates and a preparation method and application thereof, wherein the preparation process comprises the following steps:
[0112] (1) Preparation of α-Al 2 O 3 Abrasive
[0113] High purity α-Al 2 O 3 The powder is formulated into α-Al with a solid content of 30% 2 O 3 Slurry, α-Al 2 O 3 Adding α-Al 2 O 3 The powder was added with 2% potassium citrate by weight, stirred for 30 min, and sand-milled using a sand mill to obtain α-Al 2 O 3Abrasive, not α-Al 2 O 3 The abrasive was homogenized. The sanding parameters were: zirconia bead size 0.2 mm, filling rate 75 wt%, rotation speed 3000 rpm, linear speed 10.26 m / s, flow rate 120 L / h, time 80 min. The model of the sanding machine was SMP 0.5, and the manufacturer was Husong Intelligent Equipment (Taicang) Co., Ltd.
[0114] (2) Preparation of nano-alumina polishing liquid
[0115] Weigh 3490g of deionized water, add 80g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 400g of the unevenly treated α-Al 2 O 3 The abrasive was added to the stirred potassium permanganate solution, and 10 g of sodium silicate was added. After the solution was completely dissolved, 20 wt% nitric acid was used to adjust the pH of the solution to 9. After stirring evenly, a nano-alumina polishing liquid (polishing liquid: α-Al2O3 with a potassium permanganate content of 2.0 wt% and unevenly treated) was obtained. 2 O 3 The abrasive content is 2 wt%, the aluminum nitrate nonahydrate content is 0.25 wt%, the calcium nitrate tetrahydrate content is 0.25 wt%, and the sodium silicate content is 0.25 wt%).
[0116] The Si surface of the silicon carbide substrate was chemically mechanically polished using 4 kg of the prepared nano-silica sol polishing liquid, with a polishing pressure of 10.873 psi, a lower plate speed of 40 rpm, a polishing liquid flow rate of 1 L / min, and a polishing time of 1 h. The polishing pad was a non-woven polishing pad of model NWS-85 from Quzhou Bolai Narun Electronic Materials Co., Ltd. The silicon carbide substrate was a 6-inch 4H-SiC substrate from Shanxi Shuoke Crystal Co., Ltd.
[0117] 4 kg of polishing liquid was recycled and polished continuously for 4×1 h. The substrate was weighed after each hour of polishing. The MRRs were 1.231 μm / h, 1.112 μm / h, 1.076 μm / h, and 0.978 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.098 nm.
[0118] Comparative Example 3:
[0119] This comparative example provides a nano-alumina polishing liquid for silicon carbide substrates and a preparation method and application thereof, wherein the preparation process comprises the following steps:
[0120] (1) Preparation of α-Al 2 O 3 Abrasive
[0121] High purity α-Al 2 O 3 The powder was prepared into α-Al with a solid content of 30 wt%. 2 O 3 Slurry, α-Al 2 O 3 Adding α-Al 2 O 3 The powder was added with 2% potassium citrate by weight, stirred for 30 min, and sand-milled using a sand mill to obtain α-Al 2 O 3 Slurry, for α-Al 2 O 3 The slurry was subjected to gravity sedimentation for 3 days. A clear separation boundary was observed and judged. The upper clear liquid was slowly taken up with a disposable pipette, and the lower sediment was left at the bottom. The middle slurry was taken for subsequent experiments to obtain α-Al 2 O 3 Abrasive. Sanding parameters are: zirconia bead size 0.2 mm, filling rate 75 wt%, rotation speed 3000 rpm, linear speed 10.26 m / s, flow rate 120 L / h, time 80 min. The model of the sanding machine is SMP 0.5, and the manufacturer is Husong Intelligent Equipment (Taicang) Co., Ltd.
[0122] (2) Preparation of nano-alumina polishing liquid
[0123] Weigh 3760g of deionized water, add 60g of potassium permanganate, 10g of aluminum nitrate nonahydrate, and 10g of calcium nitrate tetrahydrate while stirring until they are completely dissolved, adjust the pH of the solution to 7.5 with potassium hydroxide, and then weigh 150g of α-Al 2 O 3 The abrasive is added to the stirring potassium permanganate solution, and 10g of sodium silicate is added. After it is completely dissolved, 20wt% nitric acid is used to adjust the pH of the solution to 9. After stirring evenly, a nano-alumina polishing liquid is obtained (wherein the potassium permanganate content is 2.0wt%, the alumina content is 2wt%, the aluminum nitrate nonahydrate content is 0.25wt%, the calcium nitrate tetrahydrate content is 0.25wt%, and the sodium silicate content is 0.25wt%).
[0124] The Si surface of the silicon carbide substrate was chemically mechanically polished using 4 kg of the prepared nano-silica sol polishing liquid, with a polishing pressure of 10.873 psi, a lower plate speed of 40 rpm, a polishing liquid flow rate of 1 L / min, and a polishing time of 1 h. The polishing pad was a non-woven polishing pad of model NWS-85 from Quzhou Bolai Narun Electronic Materials Co., Ltd. The silicon carbide substrate was a 6-inch 4H-SiC substrate from Shanxi Shuoke Crystal Co., Ltd.
[0125] 4 kg of polishing liquid was recycled and polished continuously for 4×1 h. The substrate was weighed after each hour of polishing. The MRRs were 1.078 μm / h, 1.112 μm / h, 1.026 μm / h, and 0.953 μm / h, respectively. The surface roughness Ra measured by atomic force microscopy was 0.086 nm.
[0126] Table 1 summarizes the removal rate and surface roughness data obtained after chemical mechanical polishing of silicon carbide substrates using materials from various embodiments and comparative examples.
[0127] Table 1 Comparison of material removal rate and surface roughness of various embodiments and comparative examples
[0128]
[0129]
[0130] According to Table 1, by comparing the above comparative examples with the embodiments, it can be found that: 2 O 3 The chemical mechanical polishing of the silicon carbide substrate by abrasive can reduce the surface roughness of the silicon carbide silicon surface while increasing the material removal rate, thereby achieving a smooth surface and improving the surface quality. The polishing abrasives used in Examples 1 to 6 are all graded aluminum oxide sanding liquids. The test results of atomic force microscopy show that Ra is less than 0.1nm. Compared with Comparative Example 1, when the polishing abrasive is replaced by aluminum oxide from silicon oxide, the material removal rate of the silicon carbide substrate is significantly improved; compared with Comparative Example 2, when the polishing abrasive is replaced by ungraded α-Al 2 O 3 Abrasive replaced with graded α-Al 2 O 3 After abrasive treatment, the surface roughness of the silicon carbide substrate was significantly reduced.
[0131] Table 2 shows the particle size distribution of alumina slurry before sanding, after sanding, and after gravity sedimentation and centrifugal sedimentation of the sanded slurry, where the diameter distance = (D90-D10) / D50, which represents the particle size range of particles in the sample and the spacing or difference between different particle sizes; the physical meaning of D50 is that particles with a particle size greater than this value account for 50% of the total volume of particles, and particles with a particle size less than this value also account for 50% of the total volume of particles; the physical meaning of D10 is that particles with a particle size greater than this value account for 90% of the total volume of particles, and particles with a particle size less than this value account for 10% of the total volume of particles; the physical meaning of D90 is that particles with a particle size greater than this value account for 10% of the total volume of particles, and particles with a particle size less than this value account for 90% of the total volume of particles.
[0132] Table 2 Comparison of particle size distribution of alumina slurry before and after sand grinding and after classification in different ways
[0133]
[0134] The main difference between Example 1 and Comparative Example 3 is that the methods of sedimentation and classification of the alumina slurry after sanding are different. Example 1 is subjected to centrifugal sedimentation treatment, and Comparative Example 3 is subjected to gravity sedimentation treatment. It can be seen from Table 2 that the diameter pitch of the alumina slurry after centrifugal sedimentation treatment is 0.6, and the diameter pitch of the alumina slurry after gravity sedimentation treatment is 1.31. After the alumina particles with small diameter pitch are used as abrasives for chemical mechanical polishing of the silicon surface of the silicon carbide substrate, the surface roughness of the silicon surface is smaller, indicating that its surface is smoother and the surface quality is higher.
[0135] Both centrifugal sedimentation and gravity sedimentation apply force to particles to separate particles of different sizes. The larger the particle size, the faster the sedimentation speed. The centrifugal effect is stronger than the gravity effect, and gradient separation of particles of different sizes can be achieved in a short time. The main purpose of sedimentation separation is to remove larger particles in D90-D100, because the presence of these particles will cause scratches to the surface of the silicon carbide substrate to varying degrees. After centrifugal separation, the D100 of alumina particles is smaller than that of gravity separation. Therefore, after chemical mechanical polishing of silicon carbide, its surface roughness value is lower and the surface quality is better.
[0136] The polishing liquid prepared by the present invention can meet the polishing requirements of high-precision workpieces in some industries, and the adjustment of the dosage of these components also falls within the protection scope of the present invention.
[0137] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A nano-alumina polishing liquid for silicon carbide substrate, characterized in that: The invention comprises 0.5wt% to 6.0wt% of α-Al2O3 abrasive, 0.5wt% to 5.0wt% of oxidant, 0.1wt% to 1.0wt% of co-oxidant, 0.05wt% to 0.5wt% of pH regulator, 0.10wt% to 0.50wt% of dispersant, and the balance is water; The α-Al2O3 abrasive has a D10 of 0.100-0.140 μm, a D50 of 0.180-0.230 μm, a D90 of 0.240-0.300 μm, a D100 of 0.340-0.420 μm, and a diameter distance of 0.6-0.
9.
2. The nano-alumina polishing liquid for silicon carbide substrate according to claim 1, characterized in that: The preparation method of the α-Al2O3 abrasive comprises: preparing α-Al2O3 powder into α-Al2O3 slurry, adding potassium citrate and then grinding, and homogenizing the ground α-Al2O3 slurry to obtain the α-Al2O3 abrasive.
3. The nano-alumina polishing liquid for silicon carbide substrate according to claim 2, characterized in that: The solid content of the α-Al2O3 slurry is 20% to 50%; The mass of the potassium citrate is 1% to 5% of the mass of the α-Al2O3 powder.
4. The nano-alumina polishing liquid for silicon carbide substrate according to claim 2, characterized in that: The specific parameters of the frosting are: zirconia bead size 0.1-0.6 mm, filling rate 70%-85%, rotation speed 1000-3500 rpm, linear speed 5-10 m / s, flow rate 80-120 L / h, time 80-150 min.
5. The nano-alumina polishing liquid for silicon carbide substrate according to claim 2, characterized in that: The specific process of the homogenization treatment is: taking the frosted α-Al2O3 slurry and centrifuging it at 1000-3000rpm for 1-10min, obtaining an upper slurry, a middle slurry and a lower slurry after centrifugation, taking the middle slurry for filtering, and the filtered product is the α-Al2O3 abrasive; The average particle size of the upper slurry is less than 100 nm, the average particle size of the middle slurry is 100-250 nm, and the average particle size of the lower slurry is greater than 250 nm; The filtration includes primary filtration and secondary filtration, wherein the primary filtration is filtration using a filter bag, and the secondary filtration is filtration using a microporous filter element.
6. The nano-alumina polishing liquid for silicon carbide substrate according to claim 1, characterized in that: The oxidant includes potassium permanganate, sodium permanganate, sodium persulfate, hydrogen peroxide, and ammonium hypochlorous acid; The pH regulator includes nitric acid, potassium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium tetraborate; The dispersant includes sodium hexametaphosphate, sodium silicate, potassium citrate, sodium polyacrylate, sodium salt of maleic acid acrylic acid copolymer, and polyethylene glycol; The co-oxidant includes calcium nitrate.
7. A method for preparing a nano-alumina polishing liquid for a silicon carbide substrate according to any one of claims 1 to 6, characterized in that: The alpha-Al2O3 abrasive, oxidant, co-oxidant, pH regulator, dispersant and water are stirred according to mass percentage and mixed evenly to obtain nano-alumina polishing liquid.
8. An application of nano-alumina polishing liquid for silicon carbide substrate, characterized in that: The silicon carbide substrate is chemically mechanically polished using the nano-alumina polishing liquid described in any one of claims 1 to 7.
9. The use of a nano-alumina polishing liquid for a silicon carbide substrate according to claim 8, characterized in that: The specific parameters of the chemical mechanical polishing are: polishing pressure of 10-15 psi, lower plate rotation speed of 20-60 rpm, polishing liquid flow rate of 0.5-1.5 L / min, and polishing time of 0.5-5 h.
10. A silicon carbide substrate, characterized in that: The nano-alumina polishing liquid described in any one of claims 1 to 7 is used for chemical mechanical polishing, and the surface is cleaned after the chemical mechanical polishing is completed to obtain a silicon carbide substrate.
Citation Information
Patent Citations
Polishing powder for polishing silicon carbide wafer, preparation method of polishing powder and polishing solution
CN111073520A
High-precision alumina polishing solution and preparation method thereof
CN101831244A
Chemical mechanical polishing composition and polishing method thereof
CN117511415A
Aluminum oxide / silicon oxide composite abrasive for polishing silicon carbide, polishing solution, preparation method and application
CN117777950A
CMP (chemical mechanical polishing) solution for polishing single crystal silicon carbide substrate and preparation method of CMP solution
CN117987016A
Cited By
Alumina CMP (Chemical Mechanical Polishing) solution for roughly polishing silicon carbide wafer and polishing method thereof
CN120173513A
Electrochemical mechanical polishing composition, application thereof and silicon carbide wafer
CN121204798A
Electrochemical mechanical polishing compositions and their applications, silicon carbide wafers
CN121204798B
Polishing solution for finely polishing silicon carbide as well as preparation method and application of polishing solution
CN121851907A